Tocilizumab Was Effective in Repairing the Large Geode in a Patient with Rheumatoid Arthritis. (25th August 2020) - Izumiyama, Takuya; Mori, Yu; Itoi, Eiji
Abstract : Rheumatoid arthritis is characterized by multiple chronic arthritis subsequently inducing joint destruction. Although subchondral geode is a well-known feature of high-disease activity, a large geode is rare. Moreover, the treatment effect of biologic agents in the repair of large geode has not been reported. The present report shows the significant effect of interleukin-6 receptor blocker, tocilizumab, in repairing the large geode in the left humeral lateral epicondyle. This case implies that tocilizumab might be an effective treatment in patients with rheumatoid arthritis even with large geode.